Generation Algorithm of a Novel Platform Attached Support Structure for FDM-Fused Deposition Modeling - Ning Lv; Yunxu Li; Yujing Qiao (Advances in Materials Science and Engineering)
In the process of 3D printing, the setting of the initial layer is the most important step to achieve perfect printing results, and its main function is to prevent warping in 3D printing. There are three main types of the first layer: Raft, Brim, and Skirt. The Brim is a special skirt and is usually the preferred starting layer for the printing process. In order to increase the adhesion, multiple Brim contour edges will be printed, which increases the difficulty of removal. Otherwise, poor adhesion effect will occur. By analyzing the distinction between inner and outer contours of polygons, the offset process of contour points in different cases is calculated in this paper, and a simplified processing method of contour offset line is designed by using the idea of Douglas–Peucker simplifying curve feature points. According to the functional characteristics of the Brim edge structure, a novel platform attached support structure is generated based on ray-casting algorithm and contour offset algorithm. The proposed algorithm is encapsulated into the slicing engine and compared with three common initial layer structures for conducting part printing comparison experiments. The experimental results show that the edge structure realized by the proposed generation optimization algorithm of a novel platform attached support can effectively reduce the slicing execution time, and the auxiliary structure has little impact on the forming quality. It can be easier to remove on the premise and the warpage of the printing model is small.